PENGARUH SENAM AEROBIK INTENSITAS SEDANG TERHADAP KADAR ERITROSIT DAN HEMATOKRIT DARAH - Siti Baitul Mukarromah (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2010)
This research aim to to know change of rate of eritrosit value and of hematokrit at trained male and do not be trained.  Conducted practice in the form of practice of aerobic gymnastic intensity. Practice program executed by 3 times per week during 8 week. Sampel in this research is male counted 19-20 one who is taken away from by population 120 people. Research device the used is The Randomized Pretest-Posttest Control Design. In the early this research, sampel which consist of 30 people try to be divided to become 2 (2 group) by random the each group consist of 15 people. Group 1 (without treatment) and group 2 (with Treatment). Both of group given by test early (pretest) and 2 final test phase (posttest) in the form of test inspection of blood after aerobik exercise by using aerobic gymnastic during 35 minute of 2 times with active rest international during 1 minute.Practice having taken steps during 8 week, done by intake and measurement of blood intravenously in  Sports Laboratory of FIK UNNES continued by inspection of klinis in CITO Laboratory of Semarang, to know rate of Eritrosit and value of hematokrit blood. Result of the measurement processed by using statistic of diskriptif, test normalitas, homogeneity test, test Anava one band with level of signifikansi 5 %.Data analysis can be concluded that (1) practice of aerobic gymnastics intensity is earning to improve rate of eritrosit blood at male (p<0,05) compared to control, (2) practice of aerobic gymnastics intensity is improving value of hematokrit blood at control group (improvement and p<0,05) morely having a meaning  of practice group at 8 first week while  at 8 week later; then practice decreased of group, (3) There is difference of  is make-up of rate of eritrosit and change of blood hematokrit at trained with practice of aerobic gymnastic intensity is and do not be trained.